Sulfated Temperature Effects on the Catalytic Activity of CeO2 in NH3‑Selective Catalytic Reduction Conditions - Zhang, Lei; Zou, Weixin; Ma, Kaili; Cao, Yuan; Xiong, Yan; Wu, Shiguo; Tang, Changjin; Gao, Fei; Dong, Lin (Journal of physical chemistry. C, 2015)
In this work, the influence of sulfated temperature on the selective catalytic reduction of NO by NH3 over the sulfated CeO2 was investigated. The NO conversion of the sulfated CeO2 samples decreased with the increase of sulfated temperature. The fresh CeO2 and the CeO2 sulfated at different temperatures were characterized by X-ray diffraction (XRD), laser Raman spectroscopy (LRS), in situ diffuse reflectance infrared Fourier transform spectroscopy (in situ DRIFTS), thermogravimetry and differential thermal analysis (TG-DTA), H2-temperature-programmed reduction (H2-TPR), and X-ray photoelectron spectroscopy (XPS). The obtained results indicate that the sulfation process was gradually deepened, and the existence states of sulfate species over CeO2 were changed from surface sulfates to bulk-like sulfates and to bulk sulfates with raising the sulfated temperature. Meanwhile, the formed bulk-like and bulk sulfates were the main reason to result in the decrease of catalytic activity. In addition, the corresponding model was proposed to understand the interaction between sulfate species and CeO2 influenced by sulfated temperature. Finally, bulk sulfates could be eliminated by H2O washing and the NO conversion of CeO2 sulfated at 550 °C was recovered after H2O washing, which supports the proposed model.